2010
DOI: 10.1007/s11426-010-3198-6
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic structures of ionic liquids 1-ethyl-3-methylimidazolium tetrafluoroborate in water probed by the relative chemical shift

Abstract: The relative chemical shifts () were put forward to investigate the microscopic structure of 1-ethyl-3-methyl-imidazolium tetrafluoroborate (EmimBF 4 ) during the dilution process with water. The concentration-dependent  (C2)H(C4)H ,  (C2)H(C5)H and  (C4)H(C5)H were analyzed. The results reveal that the variations of the microscopic structures of three aromatic protons are inconsistent. The strength of the H-bond between water and three aromatic protons follows the order: (C2)H···O > (C4)H···O > (C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…The Koga group suggested that the influence of BMIM + cation on water structure is similar to that of fructose or increased temperature, where water molecules interact with the cation leading to the reduction of H‐bonds of bulk water region. Xu et al compared the relative chemical shifts of protons in [EMIM][BF 4 ] upon dilution with water, and found the strength of H‐bonds between water and three aromatic protons decreasing in the order (C2)H···O > (C4)H···O > (C5)H···O; they also suggested that the ion pairs of this IL are dissociated rapidly when x water > 0.9. Singh and Kumar compared the changes of OH (water) and CH (imidazoliums) vibrational stretching bands in aqueous mixtures of ILs using FT‐IR spectroscopy, and observed that the blue shift of OH bands usually increases with the IL concentration and decreases in the order of different ILs: [BMIM][CH 3 SO 4 ] > [BMIM][C 8 H 17 SO 4 ] > [BMIM][BF 4 ] > [OMIM]Cl.…”
Section: Structural Properties Of Ils and Their Aqueous Solutionsmentioning
confidence: 99%
“…The Koga group suggested that the influence of BMIM + cation on water structure is similar to that of fructose or increased temperature, where water molecules interact with the cation leading to the reduction of H‐bonds of bulk water region. Xu et al compared the relative chemical shifts of protons in [EMIM][BF 4 ] upon dilution with water, and found the strength of H‐bonds between water and three aromatic protons decreasing in the order (C2)H···O > (C4)H···O > (C5)H···O; they also suggested that the ion pairs of this IL are dissociated rapidly when x water > 0.9. Singh and Kumar compared the changes of OH (water) and CH (imidazoliums) vibrational stretching bands in aqueous mixtures of ILs using FT‐IR spectroscopy, and observed that the blue shift of OH bands usually increases with the IL concentration and decreases in the order of different ILs: [BMIM][CH 3 SO 4 ] > [BMIM][C 8 H 17 SO 4 ] > [BMIM][BF 4 ] > [OMIM]Cl.…”
Section: Structural Properties Of Ils and Their Aqueous Solutionsmentioning
confidence: 99%
“…In the investigation of the microstructure of pure ILs and their mixtures with solvent, NMR spectroscopy is the commonly used technique and has been frequently utilized to study the interactions between cation and anion, or ILs and solvent, because of its accuracy and sensitivity . Especially for 1 H NMR chemical shifts, which are closely related to chemical environments of protons and could offer us much information about microstructures of mixture conveniently, such as the intermolecular interaction and electronic perturbation caused by hydrogen bonds . Furthermore, the intermolecular interaction obtained from 1 H NMR chemical shifts could be used to predict the thermodynamic and transport properties of the mixtures coupled with certain theoretical models, indicating that 1 H NMR spectroscopy is an invaluable tool in providing benchmark to test theory and in gaining insight into the nature of structure/property relation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus we may conclude that the choice of terminal methyl hydrogen atoms of Rmim + cations as internal 1 H and 13 C references is credible for a broad set of combinations 'imidazolium IL-molecular solvent'. Nevertheless, it is only better than conventional internal referencing approach in the sense that the studied system is not perturbed by addition of a reference compound and vice versa.With respect to the interpretation of such internally referenced chemical shift variations with changing concentration, it is noteworthy to mention the work of Li et al67 who clearly introduced and illustrated for EmimBF 4 -H 2 O system the concept of 'relative chemical shift', ∆δ, as the . The corresponding concentration dependence of the relative chemical shift shows whether the nuclei of interest and reference ones experience the same changes in shielding when concentration is varied or there is some asynchronicity in the occurring changes of microenvironment of various nuclei.…”
mentioning
confidence: 99%